Methacholine-induced cough as an indicator of bronchodilator-responsive cough. (October 2020) - Ohkura, Noriyuki; Fujimura, Masaki; Hara, Johsuke; Nakade, Yusuke; Abo, Miki; Sone, Takashi; Kimura, Hideharu; Kasahara, Kazuo
Abstract: Background: Cough variant asthma (CVA) is the most common cause of chronic cough and responds well to bronchodilator therapy. Previous studies on methacholine -induced cough have shown that heightened cough response due to bronchoconstriction is a feature of CVA. The aim of this study was to assess Mch-induced cough as an indicator of bronchodilator-responsive cough (BRC). Methods: This was a single-center retrospective study of prolonged/chronic cough cases who underwent evaluation via spirometry, FeNO and bronchial challenge testing using Mch and capsaicin (C5). Resultant bronchoconstriction after Mch challenge was assessed by flow-volume curves measuring the expiratory flow of the partial flow-volume curve 40% above residual volume (PEF40 ) and FEV1 . BRC was defined as a decrease in cough with bronchodilator therapy by 30% or more on a visual analog scoring scale. Results: Of the 100 patients evaluated, 63 were diagnosed with BRC. Mch-induced cough at a decrease in PEF40 of 35% (PC35 -PEF40 ) was predictive of BRC on AUROC analysis with an AUC of 0.82 (95% CI 0.73–0.90) and cut-off of 24. The AUC for C5, FeNO and PC20 -FEV1 were 0.65, 0.47, and 0.58, respectively. Conclusion: Compared to C5, FeNO and PC20 -FEV1, Mch-induced cough better supports a diagnosis of BRC.